2019
DOI: 10.3389/fpsyg.2019.01626
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Block-Building Skills and Mother-Child Block-Building Interactions Across Four U.S. Ethnic Groups

Abstract: Play offers an unparalleled opportunity for young children to gain cognitive skills in informal settings. Block play in particular—including interactions with parents around block constructions—teaches children about intrinsic spatial features of objects (size, shape) and extrinsic spatial relations. In turn, early spatial cognition paves the way for later competencies in math and science. We assessed 4- and 5-year-old children’s spatial skill on a set of block-building constructions and examined mother-child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Moreover, since these data were collected, Suh et al. (2019) reported ethnic differences in 4‐ and 5‐year‐old children's block building skills during mother–child interactions. Increasing representation in studies of early stacking and examining stacking in ecological settings rather than only in the lab are goals for future work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, since these data were collected, Suh et al. (2019) reported ethnic differences in 4‐ and 5‐year‐old children's block building skills during mother–child interactions. Increasing representation in studies of early stacking and examining stacking in ecological settings rather than only in the lab are goals for future work.…”
Section: Discussionmentioning
confidence: 99%
“…Future longitudinal studies must include visits during this period, particularly as it relates to hand preferences, object manipulation skills, and stacking strategy. Moreover, since these data were collected,Suh et al (2019) reported ethnic differences in 4-and 5-year-old children's block building skills during mother-child interactions. Increasing representation in studies of early stacking and examining stacking in ecological settings rather than only in the lab are goals for future work.…”
mentioning
confidence: 99%
“…Though child ethnicity was included in our models, having to combine other ethnic minority groups magnified the demographic limitations of this sample. Given that prior studies have shown that parents of different ethnic group interacted differently with their children (e.g., Suh et al., 2019), these limitations further warrant more research to understand whether and how other family factors contribute to parental support that can lead to gains in children’s development…”
Section: Discussionmentioning
confidence: 99%
“…In the first, which investigated numeracy behaviors (e.g., counting, performing operations) during a grocery shopping task, maternal math support was relatively infrequent across all groups, but Dominican and African‐American mothers provided the most math‐related support (Leyva et al., 2017). In the second, which examined spatial behaviors during block building, cross‐cultural variations occurred between the two Latine groups (Suh et al., 2019). Mexican‐heritage mothers spent more time in structured building (using models and more verbal instruction) than Dominican mothers, who engaged in more free building.…”
Section: What Do We Know About Latine Family Math Engagement?mentioning
confidence: 99%